The Surge of Hypervirulent ST398 MRSA Lineage With Higher Biofilm-Forming Ability Is a Critical Threat to Clinics - Lu, Huiying; Zhao, Lin; Si, Yuanguo; Jian, Ying; Wang, Yanan; Li, Tianming; Dai, Yingxin; Huang, Qian; Ma, Xiaowei; He, Lei; Li, Min (Frontiers in Microbiology, 2021)
The global increase of community-associated (CA) infections with methicillin-resistant Staphylococcus aureus (MRSA) is a major healthcare problem. Although sequence type (ST) 398 MRSA was first described as a livestock-associated (LA) lineage, human-adapted MRSA (HO-MRSA) ST398 without livestock contact has subsequently been reported from China in our previous study and other later research. The proportion of ST398 HO-MRSA has also remarkably increased in recent years in China. Based on 3878 S. aureus isolates that were collected in a general hospital between 2008 and 2018, we identified 56 ST398 HO-MRSA isolates. The four early appearing isolates of them have been sequenced by whole-genome sequencing (WGS) in our previous study. Here, by usage of WGS on the later-appearing 52 isolates and analyzing the phylogenetic dynamics of the linage, we found that 50 isolates clustered together with the former 4 isolates, making it a main clade out of MSSA clones and other MRSA clones, although ST398 HO-MRSA evolved with multiple origins. Drug resistance and virulence gene analysis based on the WGS data demonstrated that ST398 HO-MRSA main clade exhibited a similar pattern in both parts. Furthermore, they all carried a conserved variant of prophage 3 to guarantee virulence and a short SCCmec type V element of class D to maintain considerable lower methicillin resistance. Further phenotypical research verified that the epidemic HO-MRSA ST398 displayed enhanced biofilm formation ability when keeping high virulence. The dual advantages of virulence and biofilm formation in the HO-MRSA ST398 subtype promote their fitness in the community and even in the healthcare environment, which poses a serious threat in clinical S. aureus infections. Therefore, further surveillance is required to prevent and control the problematic public health impact of HO-MRSA ST398 in the future.